Penerapan Model Keperawatan Self Care Orem pada Asuhan Keperawatan Ibu Hamil yang Mengalami Kontraksi Dini - Mardiyaningsih, Eko (Jurnal Keperawatan Maternitas, 2015)
Neonatal mortality rate in Indonesia caused prematurity reaches 70%. Premature contractions causes a preterm delivery and often occurs in 8-10% of pregnancies. By applying the model of nursing Selfcare Orem, it makes nurse more focused, systematic and it describes the role of nurses. This study aimed at applying Orem self-care nursing models in nursing care of pregnant women who experiencing premature contractions. Methods: This study used case study approach. The sample in this study was 5 respondents. The sampling technique used was purposive sampling. Results: The number of respondents who graduated from Elementary School is 4 (80%) and 2 respondents (20%) were graduated from Junior High School. Based on the type of profession, 4 respondents (80%) were housewives and 1 respondent (20%) was a private sector employee. While the pregnancy average age of respondents who experienced a premature contractions was 30 weeks. Those five respondents experiencing premature contractions due to a leukorrhea. Conclusions and Recommendations: Nurse facilitates the improvement of the clients ability to care for herself and does not put the client in a dependence position. The action given to clients includes wholly compensatory system, partially compensatory system, and supportive educative.